Islamic Education Financial Management (Study at Darur Rasyid Islamic Boarding School Aceh Singkil) - Novriadi Cibro, Andika; Kaloko, Burhanuddin; Saripuddin B, Muhammad; Syafnial; Mesiono (EDUTEC : Journal of Education And Technology, 2023)
The purpose of writing is to discuss the financial management of Islamic education at the Darur Rasyid Islamic Boarding School, Aceh Singkil, both from financial planning, financial accounting and financial evaluation and accountability. The method used in this study is a qualitative method, with the approach used is Naturalistic, as well as with triangulation techniques, then data collection techniques using documentation, interviews, and observations. The step of analyzing the data is to collect the data, reduce the data, present the data and then conclude. The results of this study are: 1. The leadership of the Islamic boarding school as top manager and treasurer prepares any programs that will be implemented and then is held together with the head of the foundation, the boarding school committee, as well as the teachers, Then determine how much the budget will be spent on program implementation. 2. There is a financial assistant unit appointed to assist the madrasah treasurer in managing education finances at Darur Rasyid Aceh Singkil Islamic Boarding School. So far, with the existence of the financial assistance unit, it can allocate and distribute Islamic boarding schools' funding sources effectively and efficiently and on target. 3. Bookkeeping or recording of education finances carried out at the Darur Rasyid Aceh Singkil Islamic Boarding School only uses the general treasury book (receipts and disbursements book). The auxiliary cash book or subsidiary ledger tends to not function properly because all receipts and expenditure records are integrated into the general cash book. The details of the cost of each component of expenditure tend to be unreported and not specifically detailed. 4. Education financial reports and accountability are prepared and addressed to foundations and all authorized parties, namely, among others, accountability reports are reported every 6 months. And using the Flat Grant financing model based on the distribution system of funds.